Nfu1 Mediated ROS Removal Caused by Cd Stress in Tegillarca granosa - Qian, Guang; Bao, Yongbo; Li, Chenghua; Xie, Qingqing; Lu, Meng; Lin, Zhihua (Frontiers in Physiology, 2017)
The blood clam Tegillarca granosa, a eukaryotic bottom-dwelling bivalve species has a strong ability to tolerate and accumulate cadmium. In our previous study, Nfu1 (iron-sulfur cluster scaffold protein), which is involved in Fe-S cluster biogenesis, was shown to be significantly up-regulated under Cd stress, as determined by proteomic analysis. To investigate the function of Nfu1 in cadmium (Cd) detoxification, the function of blood clam Nfu1 (designated as Tg-Nfu1) was investigated by integrated molecular and protein approaches. The full-length cDNA of Tg-Nfu1 is 2153 bp and encodes a protein of 272 amino acid residues. The deduced Tg-Nfu1 protein is 30kDa contains a conserved Nfu-N domain and a Fe-S cluster binding motif (C-X-X-C). qRT-PCR analysis revealed that Tg-Nfu1 was ubiquitously expressed in all examined tissues; it was up-regulated in the hepatopancreas and gill, and kept a high level from 9 to 24 h after Cd exposure (250 µg/L). Western blot analysis further revealed that the Tg-Nfu1 protein was also highly expressed in the hepatopancreas and gill after 24 h of Cd stress. Further functional analysis showed that the production of ROS was increased and Cu/ZnSOD activity was inhibited in blood clam, treated with the specific Nfu1 siRNA and Cd stress, respectively. These results suggest that Tg-Nfu1 could protect blood clam from oxidative damage caused by Cd stress.